Network Analysis of #Jokowi3period on Twitter - Laras Ayu Prastika Putri; Muhammad Rafi Zufar (Universitas Negeri Malang, 2024)
Exploring the phenomenon of Twitter social media use, with a focus on hashtags #Jokowi3Period which is currently a hot topic of conversation in Indonesia. Begins from introduction of social media technology as a form of effort to meet dynamic and advanced communication needs, this study traces the transformation of Twitter from its initial concept as a message sharing platform to become a multifunctional communication tool, information, business, public opinion, and entertainment. This study also highlights a topic that was trending some time ago, namely #Jokowi3Period, which discusses the possibility of President Joko Widodo running for office for the third period. With the Social Network Analysis (SNA) approach, this research aims to analyze the network structure in digital social movements with characteristics segmented, polycentric, and integrated. Data will be collected via social media Twitter with the help of Social Network Analysis (SNA) and the netlytic.org web application. Quantitative descriptive methods will be used, with a focus on social network analysis and hashtags. SNA was chosen because it can provide an overview of interactions between actors in communication networks. This research also involved participant observation to analyze the interactions and relationships of actors or nodes that use hashtags #Jokowi3Period on the Twitter platform. With this approach, research is expected to provide more understanding in depth about the dynamics of communication in digital social movements and contributions. Twitter is the main medium in this process.